Variasi Parameter Input Spot Welding Design Dan Perubahan Nilai Tegangan Geser Sambungan Dissimilar Stainless Steel 316 – Baja Karbon ST 41 - Wardana, IGA. Anom; Budiarsa, IN.; Antara, IGN. (Teknik Desain Mekanika, 2021)
Abstract Connection strength and spot welding characteristics are influenced by several factors such as sheet thickness, tape diameter (band size), welding time, welding current, and pressure applied during welding. This research was conducted to determine the variation of the last design input parameters on the shear strength and hardness of metal joints unlike stainless steel 316 with low carbon steel ST 41. The thickness of the 316 stainless steel plate used is 1.5 mm thick steel plate and carbon steel plate thickness low ST 41 with a thickness of 2mm. In this study, using a variety of point welding design input parameters, namely the point welding voltage used is 3.2V and 1.6V with a welding time of 1 and 2 seconds and a spot welding taper diameter of 6mm and 7mm. Based on the comparison of the specimen results from the point with machine code B the tool designed for this research and machine code A which is a competitor machine (DN-5) where the machine is the factory standard. It can be said that the tool designed with machine code B is better than the results of the test graph that has been carried out. Mechanical testing is used to test shear strength. The shear strength test used the JIS Z 3139 standard. The results showed that the best shear strength value was obtained at the welding current of the specimen code C (? 6????????, 2????????????????????, 3.2 ) with an average shear strength of 300,188 Mpa with an average strain of 0.016. Key words : Spot welding, carbon steel ST 41, stainless steel 316, shear test